Jehoiachin: not a broken vessel but a humiliated vassal (Jer 22:28–30) - Crouch, C.L. (De Gruyter, 2017)
Uncertain terminology, versional differences and the juxtaposition of multiple images for Jehoiachin combine to render Jer 22:28–30 an interpretive quagmire. The article proposes to ameliorate this confusion through the emendation of the first word of v. 28, haʿæṣæb. The emended text reveals a coherent oracle, drawing on a consistent and well-established nexus of concepts associated with the consequences for vassal disloyalty.